2018
DOI: 10.1016/j.vhri.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Satisfaction Questionnaire for Medication: Validation of the Translated Arabic Version among Patients Undergoing Warfarin Therapy in Saudi Arabia

Abstract: This study provides evidence in favor of the reliability and validity of the Arabic version of TSQM 1.4 as a useful measure of satisfaction with anticoagulant therapy in patients visiting ACCs. The TSQM subscales in this patient setting seem to detect a clinically meaningful change over time, enhancing the potential of their use in routine practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 44 publications
2
9
2
Order By: Relevance
“…In our analysis, which is presented in Table 1 , the results within convergent validity revealed a significant positive correlation ( r values ranging from 0.33 to 0.61, p < 0.01) between the ACTS subscales and total scores as well as most subdomain scores of the general treatment satisfaction tool (TSQM Arabic version), which was previously validated in the patient population of Saudi ACCs. [ 19 ] These results were in contrast to those obtained in the original validation study[ 14 ] in which the degrees of association between both the ACTS subscale scores and the TSQM domains were shown to be less than expected ( r = 0.27–0.35). Conversely, the nonsignificant correlation between the ACTS Burdens subscale and the TSQM side-effects domain in the current appraisal was consistent with the original validation study.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…In our analysis, which is presented in Table 1 , the results within convergent validity revealed a significant positive correlation ( r values ranging from 0.33 to 0.61, p < 0.01) between the ACTS subscales and total scores as well as most subdomain scores of the general treatment satisfaction tool (TSQM Arabic version), which was previously validated in the patient population of Saudi ACCs. [ 19 ] These results were in contrast to those obtained in the original validation study[ 14 ] in which the degrees of association between both the ACTS subscale scores and the TSQM domains were shown to be less than expected ( r = 0.27–0.35). Conversely, the nonsignificant correlation between the ACTS Burdens subscale and the TSQM side-effects domain in the current appraisal was consistent with the original validation study.…”
Section: Discussioncontrasting
confidence: 79%
“…Previous national surveys in Saudi Arabia revealed that patients’ nonadherence scores were high[ 19 20 21 22 23 24 ] but consistent with those of other populations internationally. [ 25 26 ] Endeavors to formally measure the outcomes of anticoagulants on patient satisfaction have been inadequate and have often used unvalidated tools.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Surprisingly, lack of knowledge on basic aspects of warfarin is very high (50-70 %) [27][28][29][30][31] . Patients' non-adherence scores are also high, and their satisfaction is poor [30][31][32] , yet these are consistent with those of other international populations 12,33 . These results emphasize the need for intensive educational and awareness programs to enhance knowledge and other PROs among Saudi patients 31 .…”
Section: Introductionsupporting
confidence: 53%
“…Additionally, the generic TSQM was administered for validation purposes, owing to it being widely employed in diverse clinical settings 45 as a generic patient-satisfaction measure (the Arabic translated version has been previously validated in Saudi ACCs) 32 .…”
Section: Treatment Satisfaction Questionnaire For Medication (Tsqm 14)mentioning
confidence: 99%